2006
DOI: 10.1007/s10815-005-9013-1
|View full text |Cite
|
Sign up to set email alerts
|

Is intravenous immunoglobulins (IVIG) efficacious in early pregnancy failure? A critical review and meta-analysis for patients who fail in vitro fertilization and embryo transfer (IVF)

Abstract: Meta-analysis of three published randomized controlled trials (RCTs) of IVIG in IVF failure patients shows a significant increase in the live birth rate per woman (p = 0.012; Number Needed to Treat for 1 additional live birth, NNT = 6.0 women). Using live birth rate per embryo transferred, and adding data from two cohort-controlled trials to the meta-analysis further supports this conclusion (overall p = 0.000015, NNT = 3.7 women). Relevant variables appear to include properties and scheduling of the IVIG, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 78 publications
2
33
0
Order By: Relevance
“…IVIg appear useful in the management of women with unexplained recurrent failure to conceive following IVF/embryo transfer [89] with pregnancy rates of 56% and 9% in the groups with and without IVIg but a randomized placebo-controlled clinical trial showed no effect, while including two thirds of miscarriages in the presence of karyotype abnormalities [90]. Finally, a meta-analysis [91] of three randomized controlled trials including IVF-failure patients suggested that IVIg significantly increased the live birth rate per woman with the properties and scheduling of IVIg and the selection of patients with abnormal immune tests were relevant variables. While the risks of anaphylaxis, serum sickness, and possible prion transmission and the high costs associated with IVIg should be acknowledged, we conclude that the role of IVIg in subgroups of women with infertility remains to be determined, particularly when other approaches have failed.…”
Section: Immunoglobulinsmentioning
confidence: 99%
“…IVIg appear useful in the management of women with unexplained recurrent failure to conceive following IVF/embryo transfer [89] with pregnancy rates of 56% and 9% in the groups with and without IVIg but a randomized placebo-controlled clinical trial showed no effect, while including two thirds of miscarriages in the presence of karyotype abnormalities [90]. Finally, a meta-analysis [91] of three randomized controlled trials including IVF-failure patients suggested that IVIg significantly increased the live birth rate per woman with the properties and scheduling of IVIg and the selection of patients with abnormal immune tests were relevant variables. While the risks of anaphylaxis, serum sickness, and possible prion transmission and the high costs associated with IVIg should be acknowledged, we conclude that the role of IVIg in subgroups of women with infertility remains to be determined, particularly when other approaches have failed.…”
Section: Immunoglobulinsmentioning
confidence: 99%
“…Figure 1 shows percentage suppression of lytic activity of human PBL NK activity by three different types of IVIG at 3.125 and 6.25 mg/ml concentration in vitro. It can be seen that Gamunex was intermediate in effect compared to Gammagard (GGD), the most potent, and Gamimmune (GIM), the least potent (data for GGD and GIM as in [2]). Figure 2 shows more extensive dose-response data from three independent experiment.…”
Section: Nk Assaysmentioning
confidence: 99%
“…There is also empirical evidence for benefit in patients with recurrent spontaneous abortion if secondary or associated with autoantibodies or elevated natural killer (NK)-lineage cells in blood [2][3][4]. In vitro fertilization failure may also be prevented in patients who have immune abnormalities [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cases have often been associated with abnormalities in several different in vitro immune parameters: natural killer cell cytotoxicity, proportion of peripheral blood CD56+CD3− cells, and Th1:Th2 bias. When patients with these abnormalities are treated with immunotherapy, results have been encouraging (Carp, 2007;Clark et al, 2006;Winger et al, 2011aWinger et al, , 2011b. However, the immunological assays employed have low specificity and sensitivity (Lee et al, 2013;Thum et al, 2004).…”
Section: Introductionmentioning
confidence: 99%